PESAN KOMUNIKASI ISLAM DALAM TRADISI SYAIR TARI INAI DALAM ACARA PERNIKAHAN - Hasibuan, Muhtadiah; Arifin, Darul; Dahlan, Sabili; Sikumbang, Ahmad Tamrin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
The poem is an image that contains advice that needs to be interpreted in general. The poem also contains religious values. The poem used in the henna dance is taken from the Berjanzi, which is a poem of singing stories, Islamic stories and also prayers for the Prophet. This research aims to communicate messages in the tradition of henna dance poetry at weddings in Teluk Piai village, where henna dance poetry is sung when the bride and groom are sitting on the altar. In this research the author used the library research method (library research) at the stage of data collection, observation and interviews. The results of this research show that the henna dance poetry is a prayer chant for the prophet, where in the henna dance poetry is advice in a marriage so that it is sakinah mawaddah and warahmah.